Insulin resistance and associated factors in healthy volunteers in South-west Nigeria - EN Adejumo; OA Adejumo; OA Ogundahunsi (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2020)
Background: Insulin resistance (IR) is linked with the pathophysiology of some non-communicable diseases including Type 2 Diabetes mellitus and metabolic syndrome. Objective: To determine the factors associated with IR among apparently healthy individuals in South-west Nigeria. Methods: A cross-sectional study of a cohort of apparently healthy volunteers aged 18 years and above consecutively recruited from two communities was conducted. IR was determined using the homeostasis model assessment for IR (HOMA-IR) based on the cut off values of ≥ 2. Bivariate and multivariate analyses were used to determine the crude and adjusted odds ratio of IR associated factors. Results: A total of 520 participants aged 18-89 years were recruited for the study. Their mean age was 46.7±14.6 years and the prevalence of IR was 43.5%. Alcohol intake (AOR = 2.1, 95%CI 1.3 - 3.4; p<0.001), lack of physical exercise (AOR = 1.5, 95%CI 1.0 - 2.3), and Body Mass Index (AOR = 1.03, 95%CI 1.0 - 1.1) were the factors associated with IR. Conclusion: The prevalence of IR among apparently healthy individuals in this study was high. The need for proactive measures to avert the sequelae of IR is of utmost importance.